Transforming Society as an Environment for Social Concern and its Social-Psychological Influence on People - Mkrtumyan, Mels; Mkrtumyan, Lilit (WISDOM, 2021)
In article is rising the problem of transforming society as an environment for social concern and its social-psychological influence on people